2022
DOI: 10.3389/fmed.2022.910098
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the LZTFL1 rs11385942 Polymorphism and COVID-19 Severity in Colombian Population

Abstract: Genetic and non-genetic factors are responsible for the high interindividual variability in the response to SARS-CoV-2. Although numerous genetic polymorphisms have been identified as risk factors for severe COVID-19, these remain understudied in Latin-American populations. This study evaluated the association of non-genetic factors and three polymorphisms: ACE rs4646994, ACE2 rs2285666, and LZTFL1 rs11385942, with COVID severity and long-term symptoms by using a case-control design. The control group was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 112 publications
(114 reference statements)
0
3
0
Order By: Relevance
“…Since the beginning of the pandemic, several manuscripts have been published on risk factors associated with a mild versus a severe course of infection with SARS-CoV-2 [31][32][33][34][35]. Our limited sample size did not allow any definitive conclusions on genetic risk factors such as ABO or HLA type directly influencing clinical course.…”
Section: Discussionmentioning
confidence: 95%
“…Since the beginning of the pandemic, several manuscripts have been published on risk factors associated with a mild versus a severe course of infection with SARS-CoV-2 [31][32][33][34][35]. Our limited sample size did not allow any definitive conclusions on genetic risk factors such as ABO or HLA type directly influencing clinical course.…”
Section: Discussionmentioning
confidence: 95%
“…The biological basis of clinical variables has been discussed in previous models and reviews [123][124][125] . On the other hand, recent studies have integrated specific genetic variants into predictive models 38,126 . It is to be noted that the inclusion of variants from the IL1RN and KANSL1 genes in our model represents a novel approach.…”
Section: Total Cases Controls Cases Controlsmentioning
confidence: 99%
“…When examining genetic susceptibility to the symptoms of post-COVID-19 until March 2022, no studies were found that explored the potential link among them (18). A recent study conducted on seropositive adult patients with asymptomatic/ mild disease reported that rs11385942 polymorphism of the leucine zipper transcription factor like 1 gene (coding a protein involved in the primary cilia function and the immunological synapse between T-cells and antigen-presenting cells) was associated with disease severity but not with long-term symptoms (47). Moreover, Blankenburg et al (48) reported no significant differences between the symptoms of the SARS-CoV-2-seropositive and seronegative children, suggesting that most of the symptoms are due to lockdown syndrome rather than viral infection.…”
Section: Pathological Mechanisms Of Neurocognitive Problemsmentioning
confidence: 99%